Determination of the Optimum Docking Position for an Unmanned Underwater Vehicle using a Genetic Algorithm - Sotiropoulos, Panagiotis; Aspragathos, Nikos; Andritsos, Fivos (World Congress on Engineering 2012. July 4-6, 2012. London, UK, 2010)
An approach for the determination of the optimum docking or hovering position of an Underwater Unmanned Vehicle is proposed towards the optimum performance for a desired intervention task. An underwater scenario with a UUV equipped with a 6 DOF manipulator is examined in order to verify the applicability of the algorithm. The optimization problem is formulated taken into account primarily the manipulator dexterity as well as the distance between the current position and the optimal one and the geometric constraints imposed by the environment. The ability of the vehicle to dock in the determined optimal location is assumed. A Genetic Algorithm is designed and implemented to search for the best docking position.